2016
DOI: 10.1038/srep19442
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and radiation effects of gold nanoparticles in tumour cells

Abstract: Gold nanoparticle radiosensitization represents a novel technique in enhancement of ionising radiation dose and its effect on biological systems. Variation between theoretical predictions and experimental measurement is significant enough that the mechanism leading to an increase in cell killing and DNA damage is still not clear. We present the first experimental results that take into account both the measured biodistribution of gold nanoparticles at the cellular level and the range of the product electrons r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 38 publications
2
96
0
1
Order By: Relevance
“…RDDs calculated by Geant4 Monte Carlo simulations have been utilized in radiobiological models that predict cell survival. More specifically the Local Effect Model (LEM) has been implemented for the calculation of the GNP radiosensitization, demonstrating a good agreement with experimental values (McMahon et al 2011a, McQuaid et al 2016. Current GNP formulations have been shown not to enter the cell nucleus.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…RDDs calculated by Geant4 Monte Carlo simulations have been utilized in radiobiological models that predict cell survival. More specifically the Local Effect Model (LEM) has been implemented for the calculation of the GNP radiosensitization, demonstrating a good agreement with experimental values (McMahon et al 2011a, McQuaid et al 2016. Current GNP formulations have been shown not to enter the cell nucleus.…”
Section: Discussionmentioning
confidence: 74%
“…For instance, in the case of x-ray irradiation Li et al (2014) reported a dose enhancement value difference of a factor of 2 between the Penelope-2011 (Salvat et al 2011) and Geant4 code (Agostinelli et al 2003, Allison et al 2006. Moreover, dose distributions around the GNPs have been used in combination with radiobiological models (Lechtman et al 2013, Lin et al 2015, McQuaid et al 2016 in order to calculate biological endpoints such as cell survival. This interest in the nanoscale simulations raises a fundamental question; whether the physical interaction model selection can affect the predicted dose distribution around the GNP.…”
Section: Introductionmentioning
confidence: 99%
“…Several models have been developed to account for dose enhancement in cells by considering the increase in radiation energy deposition [205][206][207][208][209][210][211], due to additional energy absorption by the GNPs, as a function of their size. As expected, the energy of electrons emanating from the GNPs is inversely proportional to their diameter.…”
Section: Interaction Of Lees With Dna Bound To Gold Nanoparticlesmentioning
confidence: 99%
“…Many models [206][207][208][209][210][211] take into account localized effects of Auger-electron cascades. They consider the huge enhancement of energy deposited in the vicinity of GNPs, as arising from the considerable increase in photoelectric absorption cross section of gold in comparison to that of tissue [200,208,210,211]. The increase in this cross section produces an additional local generation of photoelectrons, Auger electrons, and characteristic X-rays [208,212].…”
Section: Interaction Of Lees With Dna Bound To Gold Nanoparticlesmentioning
confidence: 99%
“…AuNPs radio sensitization represents a novel technique in enhancement of ionizing radiation dose and its effect on biological systems. 142 From the first demonstration of AuNPs as a radiation contrast agent, AuNPs radio enhancement/sensitization has become an increasing area of investigation as an approach to increase the effectiveness of ionizing radiation in biological systems. 143 For example, dendrimers of well-defined structure have been used as templates or stabilizers to form dendrimer-entrapped AuNPs 144,145 for CT imaging applications, especially for blood pool imaging and tumor imaging.…”
Section: Aunms Based Imagingmentioning
confidence: 99%